Genetic Screening for TLR7 Variants in Young and Previously Healthy Men With Severe COVID-19 - Solanich, Xavier; Vargas-Parra, Gardenia; van der Made, Caspar I.; Simons, Annet; Schuurs-Hoeijmakers, Janneke; Antolí, Arnau; del Valle, Jesús; Rocamora-Blanch, Gemma; Setién, Fernando; Esteller, Manel; van Reijmersdal, Simon V.; Riera-Mestre, Antoni; et al. (Frontiers in Immunology, 2021)
Introduction: Loss-of-function TLR7 variants have been recently reported in a small number of males to underlie strong predisposition to severe COVID-19. We aimed to determine the prevalence of these rare variants in young men with severe COVID-19. Methods: We prospectively studied males between 18 and 50 years-old without predisposing comorbidities that required at least high-flow nasal oxygen to treat COVID-19. The coding region of TLR7 was sequenced to assess the presence of potentially deleterious variants. Results: TLR7 missense variants were identified in two out of 14 patients (14.3%). Overall, the median age was 38 (IQR 30-45) years. Both variants were not previously reported in population control databases and were predicted to be damaging by in silico predictors. In a 30-year-old patient a maternally inherited variant (c.644A>G; p.(Asn215Ser)) was identified, co-segregating in his 27-year-old brother who also contracted severe COVID-19. A second variant (c.2797T>C; p.(Trp933Arg)) was found in a 28-year-old patient, co-segregating in his 24-year-old brother who developed mild COVID-19. Functional testing of this variant revealed decreased type I and II interferon responses in peripheral mononuclear blood cells upon stimulation with the TLR7 agonist imiquimod, confirming a loss-of-function effect. Conclusions: This study supports a rationale for the genetic screening for TLR7 variants in young men with severe COVID-19 in the absence of other relevant risk factors. A diagnosis of TLR7 deficiency could not only inform on treatment options for the patient, but also enables pre-symptomatic testing of at-risk male relatives with the possibility of instituting early preventive and therapeutic interventions.